Design of a V-band low noise amplifier for passive millimeter wave imaging application. (August 2022) - Gong, Jianhao; Chen, Xi; Hu, Anyong; Miao, Jungang
Abstract: This paper presents a design methodology for wideband low noise amplifier (LNA) with flat gain and low noise figure (NF). A parallel RC network loaded stub circuit is proposed to enhance simultaneous noise and impedance matching. Moreover, the same structure is applied to compensate for transistor gain roll-off with frequency. By properly selecting the stub lengths for different stages, flat gain and low NF are obtained in wideband. The method is verified by designing a V-band 4-stage LNA based on 0.15 μm GaAs pHEMT process. The LNA features 15.2 dB average gain within 45–61 GHz bandwidth. In the required band of 51–57 GHz, the LNA achieves flat gain of 14.9 ± 0.3 dB and low NF of 2.6–4.2 dB. It consumes 30 mA current from 3 V supply and occupies area of 2 mm × 1.3 mm. Although the LNA is inherently multipurpose design, it is particularly suited for passive millimeter wave imaging due to its characteristic of high sensitivity.